Protection of mild steel in hydrochloric acid using methyl benzimidazole substituted 1, 3, 4-oxadiazole: computational, electroanalytical, thermodynamic and kinetic studies. Issue 20 (18th October 2019) - Ammal P, Rugmini; R Prasad, Anupama; K, Ramya; John, Sam; Joseph, Abraham
Abstract: The corrosion protection efficiency of MBIMOT, 5-((2-methyl-1H-benzo[d]imidazol-1-yl) methyl)-1, 3, 4 oxadiazole-2-thiol towards mild steel (MS) in HCl and its variation with inhibitor concentration, acid concentration and temperature were assessed by weight loss and electrochemical methods. Corrosion rate found to decrease with increasing the concentration of MBIMOT and increase with temperature and acid concentration. Electrochemical impedance spectroscopy studies revealed that the adsorption of MBIMOT on MS surface follow Langmuir isotherm. The mixed type behavior of MBIMOT is evidenced from the polarization curves. Various kinetic and thermodynamic parameters were calculated. The molecular level understanding of corrosion inhibition done by DFT approach revealed a preferential adsorption of thione form of MBIMOT over thiol form on MS surface.